Biomarcadores relacionados à Injúria Renal Aguda (IRA) induzida pelo veneno de Lachesis acrochorda em modelo experimental in vivo - Santos, João Victor de Almeida (2019)
Snakebite envenomation is considered a neglected tropical disease and can cause both local damage at the bite site as well as systemic effects, including acute kidney injury (AKI). The effectiveness of available therapies for AKI is hindered by delays in diagnosis and treatment, highlighting the urgent need for new biomarkers that allow for timely diagnosis of AKI. Therefore, the present study aimed to analyze changes in conventional and novel renal function markers triggered by the venom of Lachesis acrochorda in female C57BL/6 mice. After the experiment to determine the optimal intramuscular (IM) sublethal dose of venom, the animals received an IM administration of the selected sublethal dose (38.25 mg/kg) and were placed in metabolic cages. At 6, 12, 24, and 72 hours post-administration, the animals were anesthetized for blood and kidney tissue collection. Urine from the animals at each experimental time point was collected using the metabolic cage collection tubes. Biochemical analyses showed an increase in serum creatinine levels at 12 and 24 hours, and in urea levels at 6, 12, and 24 hours. The venom did not affect urine volume or creatinine clearance. Urinary protein levels increased at 72 hours. Venom exposure also caused an increase in serum creatine kinase at 6 and 12 hours. In assessing the involvement of oxidative stress in kidney tissue, the venom did not alter MDA levels but increased GSR gene transcription at 6 and 24 hours and decreased SOD1s transcription at 12 and 24 hours. The venom also altered parameters associated with tubular cell injury, such as increased fractional excretion of Na⁺ and Cl⁻ at 72 hours, increased KIM-1 (12, 24, and 72 hours) and NGAL gene transcription (6, 12, 24, and 72 hours), and decreased TIMP-2 transcription (12 and 24 hours). Furthermore, there were changes in the transcription of pro-inflammatory cytokines, with increased IL-1β (6 hours) and decreased IL-18 (12 and 24 hours). Principal component analysis of urine via 1H NMR revealed alterations in the phenotypic metabolic profile at 24 hours, including the presence of creatine, creatinine, taurine, betaine, α-glucose, β-glucose, and allantoin. Qualitative histological analysis showed that the venom caused alterations at 24 and 72 hours, such as cortical architecture loss, swelling and vacuolization of tubular epithelium, dilated ducts (sometimes with eosinophilic or amorphous luminal accumulations), degeneration of tubular epithelial cells, focal tubular necrosis, ectasia, and interstitial hemorrhage. This study suggests that L. acrochorda venom induces acute kidney injury associated with muscle damage, which is not reflected in changes in creatinine clearance or urine volume, but is evidenced by gene transcription markers and alterations in the urine metabolic profile.